Clinical Significance of Biochemical Pregnancy Loss in Recurrent Pregnancy Loss Patients: Insights From Euploid Embryo Transfers Minimizing Embryonic Bias - Yoshimitsu Kuwabara; Tatsunori Shiraishi; Ryoko Kato; Shigeru Matsuda; Akiko Sakata; Yumene Kubota; Ryoko Yokote; Kimihiko Nakao; Mirei Yonezawa; Tomoko Ichikawa; Toshiyuki Takeshita; Shunji Suzuki (Reproductive Medicine and Biology)
ABSTRACT Purpose To evaluate the clinical relevance of biochemical pregnancy loss (BPL) in recurrent pregnancy loss (RPL) patients, using data from preimplantation genetic testing for aneuploidy (PGT‐A) to minimize embryonic factors. Methods This retrospective cohort study included 52 PGT‐A cycles (48 patients) with single euploid embryo transfers between April 2020 and December 2022. Patients were stratified into three groups: Group A (ART failure without RPL, 18 cycles/17 patients), Group B (RPL following ART pregnancies, 12 cycles/10 patients), and Group C (RPL following natural pregnancies, 22 cycles/21 patients). This classification aimed to assess maternal factors contributing to BPL across different clinical backgrounds. The incidence of BPL, clinical pregnancy rate, and predictive performance of ART outcomes were analyzed, with and without BPL included, using ROC curve analysis. Results Biochemical pregnancy loss occurred in 0% (A), 25.0% (B), and 37.5% (C) of patients (p = 0.037). Incorporating BPL into miscarriage history significantly improved ART outcome prediction (AUC 0.871 vs. 0.759). Conclusion Biochemical pregnancy loss after euploid embryo transfer likely reflects maternal or endometrial pathology. Incorporating BPL into the diagnostic criteria for RPL may enhance clinical assessment and personalized care.